An AIE-active acridine functionalized spiro[fluorene-9, 9′-xanthene] luminophore with mechanoresponsive luminescence for anti-counterfeiting, information encryption and blue OLEDs. Issue 20 (4th May 2022) - Liang, Xiaozhong; Dong, Bizheng; Wang, Hua; Zhang, Zheng; Wang, Sijing; Li, Jie; Zhao, Bo; Li, Zhijun; Xing, Yifan; Guo, Kunpeng
Abstract : A tetra-acridine substituted spiro[fluorene-9, 9′-xanthene] (SFX-Ad ) compound is demonstrated as a multifunctional luminophore applied to anti-counterfeiting, information encryption, and blue OLEDs. Abstract : Multifunctional aggregation induced emission (AIE)-active luminophores have drawn great interest in materials science. In this work, a new three-dimensional (3D) luminophore of 9, 9′-dimethyl-9, 10-dihydroacridine substituted spiro(fluorene-9, 9′-xanthene) (SFX-Ad ) was synthesized and characterized. The highly twisted 3D configuration endows SFX-Ad with typical AIE activity, which exhibits weak emission in dilute solution and enhanced emission in the H -aggregate state. More importantly, the weakly emissive herringbone packing of SFX-Ad in the solid state displays mechanoresponsive luminescence (MRL) turn-on behavior, and underwent a crystal-to-amorphous transition. Based on its unique MRL behavior, using the samples of SFX-Ad in distinct luminescent states as the codes, anti-counterfeiting and information-encryption applications were realized. Additionally, taking its suitable molecular orbital energy levels and bright emission together, a blue organic light emitting diode ( λ EL = 421 nm, CIE (0.15, 0.10)) based on an SFX-Ad emitter yields a maximum current efficiency, power efficiency, and external quantum efficiency of 3.22 cd A −1, 2.30 lm W −1, and 2.58%, respectively.